An Improved Wavelet Correction for Zero Shifted Accelerometer Data - Timothy S. Edwards (Shock and Vibration)
Accelerometer data from shock measurements often contains a spurious DC drifting phenomenon known as zero shifting. This erroneous signal can be caused by a variety of sources. The most conservative approach when dealing with such data is to discard it and collect a different set with steps taken to prevent the zero shifting. This approach is rarely practical, however. The test article may have been destroyed or it may be impossible or prohibitively costly to recreate the test. A method has been proposed by which wavelets may be used to correct the acceleration data. By comparing the corrected accelerometer data to an independent measurement of the acceleration from a laser vibrometer this paper shows that the corrected data, in the cases presented, accurately represents the shock. A method is presented by which the analyst may accurately choose the wavelet correction parameters. The comparisons are made in the time and frequency domains, as well as with the shock response spectrum.